Identification of the agr Peptide of Listeria monocytogenes - Zetzmann, Marion; Sánchez-Kopper, Andrés; Waidmann, Mark S.; Blombach, Bastian; Riedel, Christian U. (Frontiers in Microbiology, 2016)
Listeria monocytogenes (Lm) is an important food-borne human pathogen that is able to strive under a wide range of environmental conditions. Its agr system was shown to impact on biofilm formation and virulence and has been proposed as one of the regulatory mechanisms involved in adaptation to these changing environments. The Lm agr operon is homologous to the Staphylococcus aureus system, which includes an agrD-encoded autoinducing peptide that stimulates expression of the agr genes via the AgrCA two-component system and is required for regulation of target genes. The aim of the present study was to identify the native AIP of Lm using a luciferase reporter system in wildtype and agrD deficient strains, rational design of synthetic peptides and mass spectrometry. Upon deletion of agrD, luciferase reporter activity driven by the PII promoter of the agr operon was completely abolished and this defect was restored by co-cultivation of the agrD-negative reporter strain with a producer strain. Based on the sequence and structures of known AIPs of other organisms, a set of potential Lm AIPs was designed and tested for PII-activation. This led to the identification of a cyclic pentapeptide that was able to induce PII-driven luciferase reporter activity and restore defective invasion of the agrD deletion mutant into Caco-2 cells. Analysis of supernatants of a recombinant Escherichia coli strain expressing AgrBD identified a peptide identical in mass and charge to the cyclic pentapeptide. The Lm agr system is specific for this pentapeptide since the AIP of Lactobacillus plantarum, which also is a pentapeptide yet with different amino acid sequence, did not induce PII activity. In summary, the presented results provide further evidence for the hypothesis that the agrD gene of Lm encodes a secreted AIP responsible for autoregulation of the agr system of Lm. Additionally, the structure of the native Lm AIP was identified.